The energetics of starburst-driven outflows at z ∼ 1 from KMOS. Issue 1 (9th May 2019) - Swinbank, A M; Harrison, C M; Tiley, A L; Johnson, H L; Smail, Ian; Stott, J P; Best, P N; Bower, R G; Bureau, M; Bunker, A; Cirasuolo, M; Jarvis, M; et al.
ABSTRACT: We present an analysis of the gas outflow energetics from KMOS observations of ∼ 529 main-sequence star-forming galaxies at z ∼ 1 using broad, underlying H α and forbidden lines of [N ii ] and [S ii ]. Based on the stacked spectra for a sample with median star-formation rates and stellar masses of SFR = 7 M⊙ yr −1 and M ⋆ = (1.0 ± 0.1) × 10 10 M⊙, respectively, we derive a typical mass outflow rate ofM_wind = 1–4 M⊙ yr −1 and a mass loading ofM_wind / SFR = 0.2–0.4. By comparing the kinetic energy in the wind with the energy released by supernovae, we estimate a coupling efficiency between the star formation and wind energetics of ϵ ∼ 0.03. The mass loading of the wind does not show a strong trend with star-formation rate over the range ∼ 2–20 M⊙ yr −1, although we identify a trend with stellar mass such that dM / d t / SFR ∝ M_^0.26± 0.07 . Finally, the line width of the broad H α increases with disc circular velocity with a sub-linear scaling relation FWHMbroad ∝ v 0.21 ± 0.05 . As a result of this behaviour, in the lowest mass galaxies ( M ⋆ ≲ 10 10 M⊙ ), a significant fraction of the outflowing gas should have sufficient velocity to escape the gravitational potential of the halo whilst in the highest mass galaxies ( M ⋆ ≳ 10 10 M⊙ ) most of the gas will be retained, flowing back on to the galaxy disc at later times.